Effect of IL-7 and IL-7R blockade on cytokine production by peripheral blood t cells from patients with psoriatic arthritis - E. A. Blinova; O. A. Angelskaya; V. A. Kozlov (Медицинская иммунология, 2024)
Psoriatic arthritis (PsA) is a chronic immune-mediated inflammatory joint disease, often associated with psoriasis. Interactions between immune cells, mainly T lymphocytes, and cells of the osteoarticular system are central in the pathogenesis of PsA. Th1, Th17 cytokines associated with the development of PsA contribute to an increase in the production of cytokines, chemokines, matrix metalloproteinases, adhesion molecules by immune cells, chondrocytes, fibroblasts, and induction of osteoclasts. That leads to the destruction of cartilage and bone tissue. Among the cytokines potentially involved in the pathogenesis of PsA, IL-7 is of particular interest. IL-7 is a T cell survival factor. However, it can promote the production of IFNγ and TNFα by T cells. IL-7 may indirectly promote osteoclast maturation and cartilage degradation. The aim was to investigate the effect of IL-7 and blockade of the α-chain of the IL-7 receptor (IL-7R) in vitro on the production of IL-5, IL-13, IL-2, IL-6, IL-9 IL-10, IFNγ, TNFα, IL-17A, IL-17F, IL-4, and IL-22 by T cells in norm and PsA.The study included 14 patients with PsA in the acute stage of the disease and 8 healthy individuals. To determine cytokines concentration, multiplex analysis was performed using flow cytometry.It was shown that IL-7 enhances the production of Th1, Th2, Th17, Th22, and Th9 cytokines in both patients with PsA and healthy individuals. The exception was IL-2 for both groups. Under the blockade of IL-7R with monoclonal antibodies, the level of IL-6 increases and production of IFNγ, TNFα, IL-17F, IL-10, IL-5, and IL-9 by donors’ cells and production of IFNγ, TNFα, IL-22, IL-2, IL-4, IL-5, IL-13, and IL-9 by cells from patients with PsA decreases relative to production of cells stimulated with IL-7. In donors, the blockade contributed to a change in the balance of Th1/Th2 cytokines: level of IL-4, IL-13 did not change on the background of a decrease in production of IFNγ, TNFα. In patients with PsA, under blockade of IL-7R the production of IL-10 remained at an increased level and concentration of IFNγ, TNFα and IL-2, which are actively involved in the tissue damage mechanisms, decreased. The obtained data indicate the prospect of using the IL-7R as a target for the treatment of psoriatic diseases.